Reconstruction of Legal Protection for Victims Against Secondary Victimization in the Examination Stage of Criminal Trials in Indonesia - Ida Apriyani; Subianta Mandala (Jurnal Sosial Teknologi, 2026)
This study aims to analyze the weaknesses of the Indonesian legal system in protecting victims from secondary victimization during criminal trials and to formulate a legal reconstruction model oriented towards protecting the dignity of victims. Secondary victimization is the repeated suffering experienced by victims due to interactions with the criminal justice process, such as the repetition of traumatic stories, cornering questions, and insensitive treatment by officers towards the victim's psychological condition. The research method used was normative juridical with a legislative and conceptual approach, through an analysis of the Criminal Procedure Code, Law Number 31 of 2014 concerning Protection of Witnesses and Victims, and Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence. The results of the study indicate that weaknesses in victim protection occur in three main aspects: the legal substance that does not regulate operational standards for victim examination, the legal structure that is not supported by the victimology competence of law enforcement officers, and a legal culture that is still influenced by victim blaming and social stigma. The proposed legal reconstruction is implemented through the integration of a victim-centered justice approach into criminal procedural law, through the establishment of victim-friendly examination norms, the development of national procedural standards, the strengthening of the capacity of law enforcement officers through victimology certification, the optimization of the role of the Witness and Victim Protection Agency, and the reform of the legal culture of the judiciary.